Exploring mechanisms for receiving and responding to citizen feedback in LMIC health system: a mixed methods evidence mapping of the Western Cape Province of South Africa - Sutherns, Tamaryn (Department of Public Health and Family Medicine, 2021)
Despite national governments striving for responsive health systems and the implementation of mechanisms and interventions to foster citizen feedback and participation in health, current evidence does not adequately address these mechanisms and interventions in low-income and middle-income countries (LMICs). This mixed method descriptive and exploratory study ‘maps' types of health system responsiveness mechanisms and their functionality in the South African health system, with a focus on the Western Cape Province, based on the available descriptive evidence. Multiple forms of data are scrutinized and synthesized to provide a deeper, contextual understanding of ´formal´ mechanisms that are constituted or mandated into South African and Western Cape policies and guidelines. This research shows that while national, provincial and district policies make strong provisions for health system responsiveness, including mechanisms to foster citizen feedback, in reality, implementation is not standardised and sometimes non-functional. Many of these mechanisms also currently exist in isolation, failing to feed into an overarching strategy of health system responsiveness, where feedback mechanisms may complement one another and lead to quality improvement in the health system. While there are cases for effective and well-functioning mechanisms for receiving and responding to citizen feedback, government on all levels is often hampered by resources and other constraints. These findings have implications for health researchers as well as national and provincial policymakers, seeking to enhance health system functioning.